Pengaruh Literasi Keuangan Dan Media Sosial Terhadap Perilaku Konsumtif Siswa (Studi Pada Siswa Kelas XI SMA Negeri 1 Padang) - Rezeki, Doni; Hayati, Annur Fitri (Universitas Negeri Padang, 2024)
This study seeks to examine the influence of financial literacy and social media on the consumption behavior of students at SMA Negeri 1 Padang. This is a quantitative research endeavor. The study population comprises eleventh-grade students specializing in Social Sciences at SMA Negeri 1 Padang for the 2023/2024 academic year. The sample size was calculated via the Yamane formula, yielding 105 samples. A stratified random sampling strategy was utilized for sample selection in a proportionate manner. The obtained data consists of primary data kinds according to established criteria. The analysis was performed via multiple regression analysis through SPSS. The results demonstrate that (1) financial literacy substantially influences the consumptive behavior of students at SMA Negeri 1 Padang, (2) social media also exerts a considerable effect on the students' consumptive behavior, and (3) the combined effect of financial literacy and social media significantly impacts the consumptive behavior of eleventh-grade students at SMA Negeri 1 Padang.